Three-dimensional misfit between Ti-Base abutments and implants evaluated by replica technique - Karina Bergamo Cardoso; Edmara Tatiely Pedroso Bergamo; Vitor De Moraes Cruz; Ilana Santos Ramalho; Lucas Fracassi De Oliveira Lino; Estevam Augusto Bonfante
Abstract An important factor affecting the biomechanical behavior of implant-supported reconstructions is the implant-abutment misfit. Objective: This study evaluated the misfit between Ti-Base abutments and implants by means of polyvinyl siloxane replica technique using microcomputed tomography (μCT). Methodology: Volumetric and linear (central and marginal) gaps of four Ti-base abutments (n=10/group): (i) Odontofix LTDA (OD), (ii) Singular Implants (SING), (iii) EFF Dental Components (EFF), and (iv) Control Group (S.I.N implants) compatible with an implant system (Strong SW, S.I.N Implants) were measured using μCT reconstructed polyvinyl siloxane replicas. Results: The results showed significantly lower volume gap for Control S.I.N (0.67±0.29 mm3) and SING (0.69±0.28 mm3) Ti-base abutments relative to OD (1.42±0.28 mm3) and EFF groups (1.04±0.28 mm3) (p<0.033), without significant difference between them (p=0.936). While gap values were homogenous in the central region, EFF presented a significantly higher marginal gap. Accordingly, the Control S.I.N and Singular Ti-base abutments showed improved volumetric and marginal fit relative to Odontofix and EFF. Conclusion: The method of manufacturing abutments influenced the misfit at the implant-abutment interface.